Effect of guar gum on selective separation of sphalerite from galena by flotation - R. K. Rath (The Institute of Materials, Minerals and Mining, 1905)
Adsorption, electrokinetic and flotation studies were carried out. The maximum density of adsorption of guar gum was obtained at pH 7.5 on sphalerite and at pH 11.5 on galena. Flotation recovery of sphalerite was reduced only marginally by the presence of guar gum in the pH range investigated, whereas recovery of galena was reduced to about 20% at pH 12. Differential flotation tests on binary mixtures indicated that 10 ppm of guar gum can depress galena and separate it from sphalerite at around pH 12.1. Co-precipitation tests confirmed the formation of a metal ion-guar gum complex in the bulk solution, suggesting that this is the precursor to adsorption. The adsorption isotherms for both minerals followed Langmuirian behaviour, but adsorption of guar gum on galena was significantly higher than on sphalerite and dissolution tests indicated that the concentration of Pb ions released from galena was an order of magnitude greater than that of Zn ions dissolved from sphalerite